Phytochemical, Toxicity, and Antimalarial Activity Methanol Extracts from Mangrove Coastal Beach Muara Badak, East Kalimantan - Usman, Usman; Masruhim, Muh. Amir; Rahmadani, Agung; Aziz, Abdul (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2025)
The purpose of this study was to determine the content of secondary metabolites, toxicity to Artemia salina, and antimalarial activity of methanol extracts of Avicennia marina, Rhizophora mucronata, and Sonneratia caseolaris leaves. Extraction of the third mangrove leaf species was done by maceration using methanol solvent. Then phytochemical test to determine secondary metabolite compounds, then toxicity test against shrimp larvae A. salina with BSLT method, and Antimalarial activity test in vitro against Plasmodium falciparum strain3D7 (chloroquine sensitive) using Giemsa staining microscopic method. Secondary metabolite compounds contained in methanol extracts of the third species of mangrove leaves are alkaloids, flavonoids, saponins, phenolics compounds, steroids, triterpenoids and tannins. The toxicity of the methanol extract from mangrove leaves of A. Marina, R. mucronata and S. caseolaris against A. salina is strong category with a LC50 value of 256.132 ± 45.63; 48.165 ± 52.25; and 104.96 ± 9.99 ppm respectively. However, the methanol extract of R. mucronata leaves was most toxic to A. salina due to its lowest LC50 value. Mangrove species R. mucronata and S. caseolaris showed activity against P. falciparum 3D7 in a fairly good category with IC50 values < 50 ?g/ml, while the activity of mangrove species A. marina against P. falcifarum 3D7 included unfavorable category with IC50 value > 50 ?g/ml. The other tissue parts of the third mangrove plant species still need to be further explored regarding their bioactivity against A. salina and P. falciparum 3D7.